Pengaruh Harga Dan Kualitas Produk Terhadap Minat Beli Konsumen Pada Landscape Coffee Di Desa Bandar Kota Pekalongan - Naufal Abid Dzakwan; Ade Ratna Sari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - The purpose of this study is to understand how product price and product quality affect the buying interest of consumers at Landscape Coffee located in Pekalongan City. This research uses a quantitative method, analyzing multiple linear regression to examine the impact of price and product quality on consumer purchase intention, which is the main variable being studied. Data was collected from 92 respondents who are customers of Landscape Coffee through a questionnaire using a sampling technique called purposive sampling. The data analysis technique used is hypothesis testing with SPSS 27. The results of the study show that both price and product quality have a significant effect on consumer buying interest at Landscape Coffee in Pekalongan City, both individually and together. Based on statistical tests, for price, the t-value calculated was 5.417, which is greater than 2.808. This means that Ha1 is accepted, indicating that price has a significant effect on consumer buying interest. For product quality, the t-value calculated was 12.500, which is greater than 2.808. This means that Ha2 is accepted, indicating that product quality has an effect on consumer buying interest. When considered together, the F-value calculated was 189.177, which is higher than the F-table value of 3.10. The significance value (Sig) is 0.000, which is less than α of 0.005, indicating that H0 is rejected and Ha is accepted. This means that price and product quality together have a significant effect on consumer buying interest. This also shows that the percentage of influence of service quality and price on consumer satisfaction is 81.8%, while the remaining 18.2% is influenced or explained by other variables outside of those studied.